Clitoria ternatea RESPONSE TO VARIOUS DOSAGE LEVELS AND RHIZOBIUM INCUBATION TIME - Doni, Markarius; Suarna, I Wayan; Kusumawati, N. N. Candraasih (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 10 No 2 (2021): Pastura Vol. 10 No. 2 Tahun 2021DO - 10.24843/Pastura.2021.v10.i02.p09, 2021)
This study aims to determine the response of Clitoria ternatea L. to various dose levels and incubation time of Rhizobium inoculants, as well as to determine the interaction between Rhizobium inoculant dose levels and incubation time on the response of C. ternatea plants. The experiment was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Denpasar, Bali. The experiment lasted for 3 months, using a factorial Completely Randomized Design (CRD). The first factor consists of the Rhizobium dose level, namely: 0 g kg seeds (D2), 22,5 g kg -1 of seeds (D0), 7,5 g kg-1  of seeds (D1), 15 g kg of seeds (D3), the second factor consisting of the length of the incubation period, namely: 1 hour (W1), 2 hours (W2), 3 hours (W3). Each treatment was repeated four times, so that there were 48 experimental units. The variables observed were growth variables, yield variables and characteristic variables. The results showed that there was an interaction between dose level and incubation time on the variable effective root nodules. The dose level of 22,5 g kg-1 of seeds gave the best results on variables of plant height, number of leaves, number of branches, effective root nodules, leaf dry weight, stem dry weight, root dry weight, total dry weight of forage and leaf area. The 3 hours incubation time treatment gave the highest results on the variable effective root nodules, stem dry weight and total dry weight of forage. Based on the results of the study, it can be concluded that there was an interaction between the Rhizobium dose level and the incubation time on the variable effective root nodules and the Rhizobium dose level treatment of 22,5 g kg -1 of seeds and the length of time of 3 hours gave the best effect on C. ternatea. Key words: Clitoria ternatea, Rhizobium inoculant dose, incubation time